Pengaruh Brand Awareness dan Brand Image Terhadap Keputusan Pembelian Pada Shopee di Kota Denpasar - Dewi, Santika; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The purpose of this study was to find out how the influence of brand awareness and brand image on purchasing decisions either partially or simultaneously. The population of this research is Shopee consumers in Denpasar city with a total sample of 90 respondents. This study uses non-probability sampling with purposive sampling technique. While the data analysis technique is multiple linear regression analysis. The results showed that there was a positive and significant influence between brand awareness on purchasing decisions seen from b1 = 0.148 and the value of t - arithmetic > t - table that is 2.474 > 1.671 and sig 0.040 so that the first hypothesis is accepted. There is a positive and significant influence between brand image on purchasing decisions seen from b2 = 0.631 and the value of t - arithmetic > t - table that is 5.129 > 1.671 and sig 0.000 so that the second hypothesis is accepted. There is a simultaneous influence between brand awareness and brand image on purchasing decisions seen from the value of F - count > F - table that is 44.367 > 3.11 and sig 0.000 so that the third hypothesis is accepted.